2018
DOI: 10.1002/bkcs.11635
|View full text |Cite
|
Sign up to set email alerts
|

n‐Butyllithium (1 mol %)‐catalyzed Hydroboration of Aldehydes and Ketones with Pinacolborane

Abstract: A practical and efficient protocol for the hydroboration of aldehydes and ketones using a pinacolborane and alkyl lithium system is demonstrated. A systematic evaluation showed that 1 mol % n-butyllithium afforded catalyzed hydroboration of aldehydes and ketones in a short reaction time under ambient conditions. Excellent yield, functional group tolerance, short reaction time, low catalyst loading, and gram-scale synthesis are the salient features of the proposed protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…However, a very high chemoselectivity of imine over nitrile reduction was observed. The result of these competitive experiments were consistent ones reported using THF as solvent [13] …”
Section: Resultssupporting
confidence: 90%
“…However, a very high chemoselectivity of imine over nitrile reduction was observed. The result of these competitive experiments were consistent ones reported using THF as solvent [13] …”
Section: Resultssupporting
confidence: 90%
“…As a result, the utilization of simple, commercially available group I metal salts has been at the forefront of this research area. Several groups have recently made major advancements demonstrating that simple sodium salts (NaO t Bu, NaH and NaOH) [8][9][10] and lithium salts ( n BuLi and LiHBEt3) [11][12][13] are highly active catalysts for carbonyl reductions. The simplicity of these alkali metal species suggests that they could serve as ideal precatalysts for the development of enantioselective s-block catalyzed ketone reductions in the presence of a chiral ligand.…”
Section: Asymmetric Ketone Hydroboration Catalyzed By Alkali Metal Complexes Derived From Binol Ligandsmentioning
confidence: 99%
“…Concurrently, the Bao and An groups reported that the readily accessible n-butyllithium reagent is an extremely active catalyst for the hydroboration of a variety of aldehydes and ketones (Scheme 15). 118,119 The low catalyst loading is remarkable (even to 0.1 mol%, under solvent-free conditions). However, it should be noted that commercially available n BuLi is always marketed as a solution in alkanes.…”
Section: Hydroboration Of Unsaturated Carbon-heteroatom (O N) Moietiesmentioning
confidence: 99%